Sreča, trajnostni razvoj in pravo - Pličanič, Senko (Pravnik, 2016)
In the article, the author discusses main reasons for failure to achieve sustainable development. He believes that the main reason for that failure is the excessive and one-sided orientation of western civilization into material dimension of our lives. Behind that lies an even deeper mechanism, which controls our actions. This is human desire "to be happy". The author believes that we were not aware that the path to happiness is associated with both spiritual and material growth - not only material growth. Our obsession with material is rooted in the belief that material (economic) growth is the way to happiness. We have interfered into the environment and to the other people so recklessly primarily due to our material insatiability. However, for our lives love is essential. The path to love goes through spiritual, not only through material growth. Therefore, the author stresses out the necessity of transforming the existing development paradigm into a new one with a comprehensive view of the development, which will, in addition to the material, include the spiritual growth. We should "use" the state and the law as a main tool in in achieving happiness as our main goal. In order to achieve sustainable development we need "sustainable state" and "sustainable law".
Keywords: natural environment; okolje; okoljevarstvena politika; pravna ureditev; sustainable development; trajnostni razvoj